A non–alcohol-related case of Madelung's disease: Challenging patient with progressive jugular vein distension - Gozzo, Cecilia (Radiol Case Rep, 2021)
Madelung's disease or multiple symmetric lipomatosis (MSL) is a rare benign disease characterized by abnormal, multiple and symmetric fat depositions in the subcutaneous layer, involving head, neck, back, trunk and also upper and lower limbs. MSL may be related to alcohol abuse or metabolic disorders; it may be both silent or clinically manifest. We describe a case of a 48-yo man with β-thalassemia admitted to medicine department for neck swelling without fever or respiratory symptoms. Patient denied a history of alcoholism and laboratory exam excluded metabolic disorders. Doppler ultrasound, contrast Enhanced-CT and Magnetic Resonance Imaging exams of the neck showed a symmetric, non-encapsulated fat deposition causing extrinsic compression of the right jugular vein without thrombosis. Once excluded the possibility of malignancy, patient's history, clinical, and radiological findings suggest the diagnosis of non–alcohol-related MSL disease. Knowing MSL imaging findings and its degree is crucial to guide towards the right management. Our patient did not require surgical treatment and an US follow-up is needed in order to detect any possible evolution.